Scaling migrant worker rights : how advocates collaborate and contest state power - Bada, Xóchitl; Gleeson, Shannon, 1980- (University of California Press, 2023)
"As international migration continues to rise, sending states play an integral part in "managing" their diasporas, in some cases even stepping in to protect their citizens' labor and human rights in receiving states. At the same time, institutions such as labor unions, worker centers, legal aid groups, and other immigrant advocates are among the most visible actors holding governments of immigrant destinations accountable at the local level. The potential for a functional immigrant worker rights regime, therefore, advocates to imagine a portable, universal system of justice and human rights, while simultaneously leaning on the bureaucratic minutiae of local enforcement. Taking Mexico and the United States as entry points, Scaling Migrant Worker Rights analyzes how an array of organizations put tactical pressure on government bureaucracies to holistically defend migrant rights. The result is a nuanced, multilayered picture of the impediments to and potential realization of migrant worker rights"-- Provided by publisher.
Keywords: Foreign workers, Mexican -- Civil rights -- United States.; Migrant labor -- Civil rights -- United States.; Labor movement -- Mexico.; Labor movement -- United States.; Travailleurs étrangers mexicains -- Droits -- États-Unis.; Travailleurs migrants -- Droits -- États-Unis.; Mouvement ouvrier -- Mexique.; Mouvement ouvrier -- États-Unis.; Employment & labour law.; LAW / Labor & Employment.; Labor movement; Mexico; United States; migrants; workers; labor rights; human rights; Electronic books.